LABORATÓRIO DE CIÊNCIAS: ENSINANDO GEOGRAFIA DE UM JEITO DIFERENTE - Lourenção, Bruna Cláudia; Fernandes dos Santos Rodrigues, Fernanda; Araújo Borges, Karen; Pereira Caetano, Larissa; Rodrigues Borges, Luz Clarita; Abadia de Sousa Alves, Milena; Coelho de Souza dos Reis, Renan Gustavo (Intercursos, 2026)
não há